ChemInform Abstract: Self‐Assembly of Supramolecularly Engineered Polymers and Their Biomedical Applications. Issue 49 (9th December 2014) - Wang, Dali; Tong, Gangsheng; Dong, Ruijiao; Zhou, Yongfeng; Shen, Jian; Zhu, Xinyuan
Abstract Review: 182 refs.